(untitled) (Baghdad Science Journal, 2019)
This study was focused on biotreatment of soil which polluted by petroleum compounds (Diesel) which caused serious environmental problems. One of the most effective and promising ways to treat diesel-contaminated soil is bioremediation. It is a choice that offers the potential to destroy harmful pollutants using biological activity. Four bacterial strains were isolated from diesel contaminated soil samples. The isolates were identified by the Vitek 2 system, as Sphingomonas paucimobilis, Pentoae species, Staphylococcus aureus, and Enterobacter cloacae. The potential of biological surfactant production was tested using the Sigma 703D stand-alone tensiometer showed that these isolates are biological surfactant producers. The better results of the surface tension reduction test were obtained using the mixed bacterial culture which reduced the surface tension of the medium from 66mN/m to 33.89mN/m. For further evidence of the biodegradation effect of these isolates individually and as a mixed culture, which was supported by the use of Gas-Chromatography technology confirming the occurrence of biodegradation. The capability of mixed bacterial culture was examined to remediate the diesel contaminated soil in bio piles system. Two pilot scale bio piles (25 kg soil each) were constructed containing soils contaminated with approximately 2140 mg/kg total petroleum hydrocarbons (TPHs). Both systems were equipped with oxygen to provide aerobic conditions, incubated at ambient temperature and weekly sampling within 35 days (during summer season). Overall 75.71 % of the total petroleum hydrocarbons were removed from the amended soil and 33.18 % of the control soil at the end of study period. The study concluded that the ex-situ bioremediation (bio piles) is a good option for treating the soil contaminated with diesel as economical and environmentally friendly.